Sex Hormones and Satellite Cell Regulation in Women. (14th April 2022) - Oxfeldt, Mikkel; Dalgaard, Line Barner; Farup, Jean; Hansen, Mette
Abstract : Recent years have seen growing scholarly interest in female physiology in general. Moreover, particular attention has been devoted to how concentrations of female sex hormones vary during the menstrual cycle and menopausal transition and how hormonal contraception and hormonal therapy influence skeletal muscle tissue. While much effort has been paid to macro outcomes, such as muscle function or mass, rather less attention has been paid to mechanistic work that may help explain the underlying mechanism through which sex hormones regulate skeletal muscle tissue. Evidence from animal studies shows a strong relationship between the female sex hormone estrogen and satellite cells (SCs), a population of muscle stem cells involved in skeletal muscle regulation. A few human studies investigating this relationship have been published only recently. Thus, the purpose of this study was to bring an updated review on female sex hormones and their role in SC regulation. First, we describe how SCs regulate skeletal muscle maintenance and repair and introduce sex hormone signaling within the muscle. Second, we present evidence from animal studies elucidating how estrogen deficiency and supplementation influence SCs. Third, we present results from investigations from human trials including women whose concentrations of female hormones differ due to menopause, hormone therapy, hormonal contraceptives, and the menstrual cycle. Finally, we discuss research and methodological recommendations for future studies aiming at elucidating the link between female sex hormones and SCs with respect to aging and training.